2018
DOI: 10.2214/ajr.17.19134
|View full text |Cite
|
Sign up to set email alerts
|

JOURNAL CLUB: Evaluation of Diffusion Kurtosis Imaging of Stroke Lesion With Hemodynamic and Metabolic MRI in a Rodent Model of Acute Stroke

Abstract: The present study confirms that DKI provides an expedient approach for refining the heterogeneous DWI lesion that is associated with graded metabolic derangement, which is promising for improving the infarction core definition and ultimately helping to guide stroke treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 50 publications
(52 reference statements)
3
21
0
Order By: Relevance
“…This finding confirmed that the MK-and MD-mismatched region represents tissues with less damage that should concern the doctor and attempted to be rescued. Weber et al 32 and Lu et al 33 also confirmed that the mismatched regions can return to normal levels.…”
Section: Discussionmentioning
confidence: 87%
“…This finding confirmed that the MK-and MD-mismatched region represents tissues with less damage that should concern the doctor and attempted to be rescued. Weber et al 32 and Lu et al 33 also confirmed that the mismatched regions can return to normal levels.…”
Section: Discussionmentioning
confidence: 87%
“…The ischemic diffusion lesion was automatically segmented from the ADC map using a K-means clustering algorithm of two clusters, with the label for the ischemic lesion automatically identified as the cluster of a reduced ADC. 44 The ipsilateral ischemic lesion was mirrored to the contralateral brain along the midline. 22 The pH-specific MRAPT analysis (ΔMRAPTR) is calculated as the difference between R 1 -scaled MTR asym and an estimated baseline image that is not pH-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, APT‐weighted images were processed using MTR asym )(I-3.5ppm-I+3.5ppmI0, T 1 ‐normalized MTR asym )(R10.166667em·0.166667emI)(-3.50.166667emppm-I)(+3.50.166667emppmI0, and AREX )(R1cos2θ0.166667em·0.166667em)(I0I)(+3.50.166667emppm-I0I)(-3.50.166667emppm. The ischemic diffusion lesion was automatically segmented from the ADC map using a K‐means clustering algorithm of two clusters, with the label for the ischemic lesion automatically identified as the cluster of a reduced ADC 44 . The ipsilateral ischemic lesion was mirrored to the contralateral brain along the midline 22 …”
Section: Methodsmentioning
confidence: 99%
“…The mean MTR (MMTR) and MTR asym was calculated as 1-Iitalicref+Iitaliclabel2I0 and Iref-IlabelI0, respectively, where I ref and I label are the reference (−3.5 ppm) and label (+3.5 ppm) scans while I 0 is the control image without RF saturation. The ischemic diffusion lesion was automatically segmented from the ADC map using the K‐means clustering algorithm . We calculated the contrast‐to‐noise ratio (CNR) as the ratio of the difference and standard deviation from the ischemic lesion and the contralateral normal tissue.…”
Section: Methodsmentioning
confidence: 99%